Analisa Variabel Kegagalan Kontraktor Di Kota Pekanbaru Dalam Proses Evaluasi Pengadaan Barang Dan Jasa Pemerintah Secara Elektronik (E- Procurement) - Ni Wahyu Dyah; Ryan Tri Komara; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
E-procurement is a process of procuring goods and services which is done electronically (internet/web based). One of the steps worth noted in construction project is the process ofcontractor appointment. Usually, such process is conducted through the auction of services and goods procurement. The auction is currently regulated in Presidential Regulation of 2012Number 70 about the second amendment of Presidential Regulation of 2010 Number 54 about Procurement of Government Services and Goods. In accordance to the regulation, this research aims to identify failure variables that can affect the process of evaluation for construction services auction in government owned project especially in Pekanbaru, Riau. Data in thisresearch is obtained from interview with the Head of ULP and LPSE of Riau Province and also secondary data obtained from LPSE of Riau Province’s website that comprise of documents regarding the implementation of the auction especially in road and pavement constructionservice on 2011, 2012 and 2013. The method used to process the data is manual process using software aid of Microsoft Excel, pie chart and bar chart. According to the result of the analysis conducted on auction for road and pavement construction service between 2011 until 2013, it can be obtained that the biggest percentage of 44 % during 2011 is for administration phase, the dominant factor of contractor failure because they were not uploaded document of demand.In 2013, the biggest percentage of 48 % of the contractor failure caused by technical problems inconstruction method and where in 2013 with the same the dominant factor of contractor failure increased to 50 %.Keywords: E-procurement, failure factor, auction, services and goods procurement system